LMO2 is essential to maintain the ability of progenitors to differentiate into T-cell lineage in mice - Ken-ichi Hirano; Hiroyuki Hosokawa; Maria Koizumi; Yusuke Endo; Takashi Yahata; Kiyoshi Ando; Katsuto Hozumi (eLife, 2021)
Notch signaling primarily determines T-cell fate. However, the molecular mechanisms underlying the maintenance of T-lineage potential in pre-thymic progenitors remain unclear. Here, we established two murine Ebf1-deficient pro-B cell lines, with and without T-lineage potential. The latter expressed lower levels of Lmo2; their potential was restored via ectopic expression of Lmo2. Conversely, the CRISPR/Cas9-mediated deletion of Lmo2 resulted in the loss of the T-lineage potential. Introduction of Bcl2 rescued massive cell death of Notch-stimulated pro-B cells without efficient LMO2-driven Bcl11a expression but was not sufficient to retain their T-lineage potential. Pro-B cells without T-lineage potential failed to activate Tcf7 due to DNA methylation; Tcf7 transduction restored this capacity. Moreover, direct binding of LMO2 to the Bcl11a and Tcf7 loci was observed. Altogether, our results highlight LMO2 as a crucial player in the survival and maintenance of T-lineage potential in T-cell progenitors via the regulation of the expression of Bcl11a and Tcf7.